Renal Transplant from Living Donor in a Patient of Very High Surgical Risks Due to Takayasu Disease and Several Course of Vascular Thrombosis. (July 2018) - Jiménez, Sara; Fernández, Ana María; Galeano, Cristina; Elías, Sandra; Burgos, Francisco Javier; Gómez, Victoria; Liaño, Fernando
Abstract : Introduction: Takayasu arteritis is a vasculitis of large vessels that produces inflammation and stenosis of medium and large caliber arteries affecting mainly the aorta. It is an uncommon cause of terminal kidney disease. Patient and Methods: A 33-year-old man with Takayasu's disease diagnosed in 2000. He presented hypertensive emergency that required left renal autotransplantation in 2002 with early thrombosis wich required nephrectomy. Angioplasty on right renal artery in 2005. Critical stenosis of the celiac trunk, superior mesenteric and right renal artery pseudoaneurysm with aorto-aortic bypass with superior mesenteric reimplantation and right aorto-renal bypass with placement of PTFE prostheses with thrombosis that required thrombectomy. Thrombosis of the aorto-renal bypass resolved by fibrinolysis. Aortic prosthesis rupture with thrombosis of right aorto-renal bypass and critical stenosis of superior and inferior mesenteric artery and of the celiac trunk resolved by aortic-aortic endoprosthesis implantation and by right common iliac artery to superior mesenteric and from this to right renal. In the postoperative period, he presented with acute renal failure, remaining in a pre-dialysis situation. In October 2016, a kidney transplant was performed from a living donor (mother) to the right iliac fossa with vascular anastomosis from the end to the external iliac. Results: When channeling the central line, he presented complete atrio-ventricular block with escape rhythm. He required atropine, isoproterenol, cardiopulmonary resuscitation and pacemaker implantation. Immunosuppressed with thymoglobulin, tacrolimus, mycophenolate and steroids with decreased creatinine in the immediate post-transplant. Given the antecedents, prior to transplantation, low molecular weight heparin was started, which was maintained for a month, and subsequently antiaggregation with acetylsalicylic acid. One year later, she presented a functioning graft with creatinine of 1.3 mg / dl and Doppler ultrasound with good renal perfusion and normal spectral recording. Conclusion: Live donor transplantation should be an alternative to assess in patients with high surgical risk. Adequate antithrombotic prophylaxis and individualized immunosuppressive regimen is necessary in these patients.